Involuntary Resettlement Sourcebook : Planning and Implementation in Development Projects, Additional Appendices (from CD-ROM) - World Bank (Washington, DC, 2013)
The book clarifies many policy, and technical issues that confront resettlement policymakers, and practitioners. It provides guidance on resettlement design, implementation, and monitoring, and, it discusses resettlement issues particular to development projects in different sectors, such as urban development, natural resource management, and the building of dams. Construction of infrastructure, a prerequisite for sustained socioeconomic growth, often requires the acquisition of land, and therefore, the physical relocation, and economic displacement of people. If such impacts, collectively characterized as involuntary resettlement, are not identified, and adequately mitigated, some already vulnerable populations are likely to be further impoverished, thereby undermining the objectives of the development process. Integration of involuntary resettlement issues into development projects facilitates expeditious project implementation, and improves incomes and living standards of affected populations.